2015
DOI: 10.1128/jvi.03674-14
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Infection Interferes with the Maintenance and Differentiation of Trophoblast Progenitor Cells of the Human Placenta

Abstract: Human cytomegalovirus (HCMV) is a major cause of birth defects that include severe neurological deficits, hearing and vision loss, and intrauterine growth restriction. Viral infection of the placenta leads to development of avascular villi, edema, and hypoxia associated with symptomatic congenital infection. Studies of primary cytotrophoblasts (CTBs) revealed that HCMV infection impedes terminal stages of differentiation and invasion by various molecular mechanisms. We recently discovered that HCMV arrests ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 125 publications
5
62
0
Order By: Relevance
“…It has also been reported that HCMV infection inhibits differentiation of trophoblast progenitor cells. 23 Collectively these data suggest that HCMV inhibits host cell differentiation programs, possibly to allow for lytic replication. However, the molecular mechanisms remain to be defined.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…It has also been reported that HCMV infection inhibits differentiation of trophoblast progenitor cells. 23 Collectively these data suggest that HCMV inhibits host cell differentiation programs, possibly to allow for lytic replication. However, the molecular mechanisms remain to be defined.…”
Section: Discussionmentioning
confidence: 97%
“…The inhibition of differentiation by HCMV appears to be common among progenitor cells infected by this virus. 22,23 Smirnov et al, 24 show that adipogenesis and osteogenesis are inhibited with HCMV infection in bone marrowderived MSCs. 24 They also show that MSCs are susceptible to HCMV infection at different stages of differentiation although infection kinetics are reduced in a timedependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies of HCMV infection in the human placenta revealed important differences in infection between cell types [15][16][17][18][19] and maternal immune status 7,8,16,20 . Studies of primary human placental cells and tissue models have identified molecular pathways that impair trophoblast differentiation [17][18][19][21][22][23][24] .…”
Section: Under the Microscopementioning
confidence: 99%
“…Studies of primary human placental cells and tissue models have identified molecular pathways that impair trophoblast differentiation [17][18][19][21][22][23][24] . Patterns of viral proteins in infected placentas suggest modulation of infection in early Since the attenuated and clinical strains exhibited markedly distinct levels of infection in placental explants, the differences were quantified by counting the number of cytotrophoblasts expressing IE1…”
Section: Under the Microscopementioning
confidence: 99%